Risk factors for bacteremia following endoscopic retrograde cholangiopancreatography - Tümtürk, Ayhanım; Ataman Hatipoglu, Cigdem (Journal of Surgery and Medicine, 2020)
Aim: Bacteremia after endoscopic retrograde cholangiopancreatography (ERCP) is a serious complication, but its risk factors have not yet been clearly defined. In this study, we aimed to determine the incidence of bacteremia and associated risk factors after ERCP. Methods: This retrospective-cohort study was conducted between January 2017 and December 2018. Patients who had no signs of infection before the procedure and who developed bacteremia after the procedure were included in the study. For each patient who developed bacteremia, two randomized control patients who underwent ERCP and did not develop bacteremia were selected to compare risk factors, clinical and laboratory findings. Results: A total of 91 bacteremia attacks were detected in 86 of the 4237 patients who underwent ERCP procedure. Bacteremia rate after ERCP was 2%. In multivariate analysis, the age of the patient, presence of biliary tract cancer, cholecystitis / cholangitis, pancreatitis and biopsy were determined as significant risk factors for post-ERCP bacteremia (P=0.009, P<0.001, P=0.008, P=0.002 and P=0.014 respectively). Conclusion: The development of bacteremia after ERCP significantly increases the risk of mortality. The mean age of the patients who died was older. This result supports the use of prophylactic antibiotics especially in elderly patients. We think that knowledge of potential ERCP complications and risk factors may help reduce the incidence and severity of complications.